INTERNET GAMING DISORDER – A DESCRIPTION OF THE RESEARCH AND A PROPOSAL TO CORRECT IMPROPER ATTITUDES - Magdalena Cyrklaff-Gorczyca; Tomasz Kruszewski (Rozprawy Społeczne)
Introduction The aim of the article is to present research on potential determinants of gaming disorder